Income Inequality and Gender in New Zealand, 1998-2003 - Kerry L. Papps (Institute for the Study of Labor (IZA), 2004)
A number of authors have documented an increase in earnings or income inequality in New Zealand during the late 1980s and early 1990s, a period of major economic reform, however no study has evaluated changes in inequality during the post-reform era. This paper applies a recently-developed method for decomposing changes in inequality to New Zealand income and earnings data and extends it to analyse changes in inequality between men and women. Across the total working-age population, income inequality rose among both males and females between 1998 and 2003. In both cases, the majority of this was unexplained by changes in the observed determinants of income, however shifts in the distribution of education and the associated returns were responsible for part of the increase. Among the subset of workers, earnings inequality increased significantly for both genders. Although changes in the returns to measured characteristics contributed to the rise in inequality, this was partially offset by changes in the distribution of these characteristics. Between-gender inequality fell with respect to both samples. In contrast to within-gender inequality, this was largely explained by changes in the returns to the observed characteristics. Overall, there is evidence that the male and female income distributions are converging, although both are becoming more dispersed.
Keywords: J3; 330; income inequality; gender; labour force structure; Lohnstruktur; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Qualifikation; Bildungsertrag; Schätzung; Neuseeland